THU0472 Amino Acid Position 10 in the HLA-DRB1 Protein Associates with Radiological Erosions in Early Active RA. (10th June 2014) - Scott, I.C.; Quist, J.; Spain, S.L.; Tan, R.; Steer, S.; Cope, A.P.; Lewis, C.M.
Abstract : Background: Advances in imputation methods have enabled association studies of HLA protein amino acid polymorphisms and rheumatoid arthritis (RA) susceptibility. A recent meta-analysis of this region has attributed most of its association with seropositive RA to 5 amino acid positions [1]. Radiological progression in RA has a significant genetic component. Previous studies have linked shared-epitope alleles to radiological damage in RA; the association between HLA amino acid polymorphisms and radiological progression is unexplored. Objectives: To evaluate the relationship between HLA amino acid polymorphisms and radiological progression (defined as the development of new erosions over 2 years) in early, active RA patients enrolled to a clinical trial. Methods: The Combination Anti-Rheumatic Drugs in Early RA (CARDERA) trial randomised 467 patients to receive methotrexate with or without ciclosporin, corticosteroids or both treatments in a factorial-design. We evaluated 421 European ancestry patients with archived DNA (passing QC procedures) and radiological data available. Radiographs were evaluated 6-monthly (for 2 years) for the development of new erosions. Genotyping was performed on the ImmunoChip; HLA alleles and amino acid polymorphisms were imputed using SNP2HLA [2]. We evaluated 237 amino acid positions in 3 MHC class I and 5 MHC class II proteins and 255 HLA alleles for their association with new erosions. Association testing was performed using UNPHASED version 3.0.7, which utilises a standard retrospective likelihood model for a binary trait and allows the use of polymorphic markers [3]. A P -value threshold of 0.0002 was applied based on permutation testing. Ethical approval was obtained; all patients provided consent. Results: One amino acid position, which was position 10 in HLA-DRβ1 ( P =0.0001) passed our pre-defined significance threshold for association with new erosions. Using glutamine as the reference amino acid, the OR for new erosions with tyrosine was 0.443 (95% CI 0.278-0.706). A similar trend was observed for HLA alleles; the strongest association was seen with HLA-DRB1 *04 ( P -value=0.0002), which encodes glutamine at position 10. The absence of *04 alleles provided an OR for new erosions of 0.513 (95% CI 0.360-0.730). Conclusions: We demonstrate an association between amino acid polymorphisms at position 10 in the HLA-DRβ1 protein and the development of radiological erosions in early active RA. Unlike amino acid polymorphisms associating with RA susceptibility (located in binding grooves) this polymorphism influences β- and α-chain binding; it could therefore influence radiological damage through attenuating antigen presentation within the joint. Replication of our finding in other cohorts is required to confirm its validity. References: Raychaudhuri S et al. Five amino acids in three HLA proteins explain most of the association between MHC and seropositive rheumatoid arthritis. Nat Genet 2012 29; 44: 291-6. Jia X et al. Imputing amino acid polymorphisms in human leukocyte antigens. PLoS One 2013; 8: e64683. Dudbridge F. Likelihood-based association analysis for nuclear families and unrelated subjects with missing genotype data. Hum Hered 2008; 66: 87-98. Acknowledgements: Arthritis Research UK (Grant Reference Number 19739 to ICS); National Institute for Health Research (NIHR) Biomedical Research Centre at Guy's and St Thomas' NHS Foundation Trust in partnership with King's College London. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4069